Strontium isotopes as an indicator of human migration – easy questions, difficult answers - Szostek, Krzysztof; Mądrzyk, Katarzyna; Cienkosz-Stepańczak, Beata (Anthropological Review, 2015)
Isotope analyses of bones and teeth allow us to study phenomena which occurred in the history of human species and which are difficult to capture by traditional anthropological methods. Measuring oxygen, nitrogen and carbon isotope levels in the skeleton makes it possible to reconstruct climatic changes, diet and/or the weaning process. Among isotopes used in such analyses are strontium isotopes, helpful in analysing migration and studying the mobility of historical and prehistoric human populations. In this respect, the proportion of two isotopes, the heavier 87Sr and the lighter 86Sr, is measured, following their extraction from the bioapatite of the bone mineral. Released from rocks in the weathering process, strontium permeates individual components of inanimate and animate environments, and then finds its way, together with food, to the human body. Thanks to comprehensive environmental studies and the measurement of the strontium ratio 87Sr/86Sr in various animal tissues it is possible to determine the local isotope background for the environment. Values obtained by analysing human skeletons referenced against the range of environmental isotope variability enable researchers to trace back the location inhabited by the individual or group.